Revisiting the dengue epidemic of 2011 in Paraguay: molecular epidemiology of dengue virus in the Asuncion metropolitan area - Alejandra Rojas; Adriana Moreira Soares; Laura Patricia Mendoza; María Eugenia Acosta; Laura Aria; Malvina Páez; Lilian Herebia; María Asunción Vallejos; Yvalena de Guillén; Victor Hugo Aquino (BMC Infectious Diseases, 2021)
Abstract Background Dengue is one of the most important re-emerging viral diseases and the most common human arthropod-borne viral infection worldwide. Any of the four Dengue virus serotypes (DENV-1 to 4) can cause asymptomatic infections or clinical manifestations that range in severity from a mild, self-limited illness, to a severe disease characterized by a shock syndrome that can lead to death. Paraguay suffers periodic epidemic outbreaks of dengue since 1988 when the DENV-1 was introduced in the country. Epidemics caused by all four serotypes have been reported and the country. Although dengue is endemic in Paraguay, few studies have described the molecular epidemiology of DENV in the country, which is important to understand the local and global spread, as well as the evolution of this pathogen. Methods This was a cross-sectional study of a convenience sample. Suspected dengue patients of any age were recruited from the Emergency Laboratory of the Central Hospital of the Institute of Social Welfare, Asuncion, Paraguay, from February to June of 2011. A DENV antigen test was used to confirm the infection. The protein E gene sequences of isolated viruses were sequenced for phylogenetic analysis. Results Dengue was confirmed in 55.1% of the participants (n = 98/178). The most frequent clinical findings were fever, headache, and myalgia. Identity analyses of the protein E gene sequence of 56 viruses isolated showed the circulation of DENV-1 (n = 45) and DENV-2 (n = 11) in the Asuncion metropolitan area in 2011. Molecular epidemiology analyses suggest that DENV-1 was introduced into Paraguay from Argentina, while the DENV-2 from Brazil, replacing previous virus lineages. Conclusions We have analyzed the molecular epidemiology of DENV-1 and DENV-2 isolated in Paraguay in 2011. We found strong evidence that DENV-1 was introduced into Paraguay from Argentina, while the DENV-2 from Brazil, replacing previous virus lineages. Molecular epidemiology studies are of great interest to analyze the dynamic of DENV spread, which are useful for early implementation of containment measures to reduce the risk of explosive epidemics caused by this virus.